PROSOCIAL NEEDS AND EXPERIENCE OF FUTURE PHYSICAL EDUCATION TEACHERS IN THE PROCESS OF PROFESSIONAL EDUCATION AT THE UNIVERSITY - Eroshenkova, E.I.; Isaev, I.F.; Irkhina, I.V.; Irkhin, V. N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the prosocial needs and experience of future physical education teachers in the process of professional education at the university. Methods and structure of the study. The experiment was conducted on the basis of the Faculty of Physical Education of the Belgorod State National Research University in 2021 with the participation of 87 students of pedagogical areas of training based on the online survey "Prosocial practices of the future teacher" (E.I. Eroshenkova), the application of the methods "Social norms of prosocial behavior" ( I.A. Furmanov, N.V. Kukhtova), “Measuring prosocial tendencies” (G. Carlo and B.A. Randall), questionnaires “Tactics of accumulating social capital” (A.L. Sventsitsky, T.V. Kazantseva). Results and conclusions. It was established that students in the process of professional education at the university acquired pro-social experience of participation in the practices of patronage, tutoring, volunteering; expanded the “pro-social” network of helping others; increased the degree of pro-social activity in sports, leisure, educational and developmental, health-oriented activities. In the process of studying at a university, when communicating with teachers and students, future teachers of physical culture prefer to use the tactics of "expressing sympathy", "openness", "assistance". The obtained results fix the effectiveness of the pro-social vector of professional education carried out at the university.